IoT-Based Seaweed Cultivation Monitoring System with Data Transmission Protection Using JSON Web Token (JWT) on ESP32 - Iwan Fitrianto Rahmad; Yudho Andika; Vidi Agung Fragastia; Elsa Aditya (LPPM Universitas Potensi Utama, 2026)
Security in the communication of IoT devices is a critical concern in seaweed cultivation monitoring systems, particularly when operating over open networks. This study presents the design and implementation of an IoT-based monitoring system for seaweed cultivation, incorporating data transmission protection on the ESP32 device through the use of JSON Web Token (JWT). The system monitors key parameters influencing seaweed growth—such as temperature, salinity, pH, and turbidity—and transmits this data to a server via HTTP/HTTPS protocols. JWT is employed for authentication and authorization, ensuring that only legitimate devices are permitted to send data to the server. The research methodology encompasses requirement analysis, system architecture design, hardware and software implementation, followed by functionality, security, and performance testing. Experimental results demonstrate that the proposed system successfully acquires sensor data and transmits it in real time to the server, while effectively rejecting unauthorized attempts lacking valid tokens. The application of JWT significantly enhances communication security with minimal impact on ESP32 performance. Overall, the proposed IoT-based Seaweed Cultivation Monitoring System with JWT protection provides an effective solution for safeguarding data integrity and authenticity in seaweed farming applications.